2007
DOI: 10.1126/science.1137165
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Panton-Valentine Leukocidin Causes Necrotizing Pneumonia

Abstract: The Staphylococcus aureus Panton-Valentine leukocidin (PVL) is a pore-forming toxin secreted by strains epidemiologically associated with the current outbreak of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) and with the often-lethal necrotizing pneumonia. To investigate the role of PVL in pulmonary disease, we tested the pathogenicity of clinical isolates, isogenic PVL-negative and PVL-positive S. aureus strains, as well as purified PVL, in a mouse acute pneumonia model. Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
532
5
21

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 667 publications
(571 citation statements)
references
References 18 publications
13
532
5
21
Order By: Relevance
“…Broadspectrum immunosuppression with systemic cyclophosphamide and impairment of mucociliary clearance with intranasal formalin also allow for development of S. aureus pneumonia, independent of bacterial toxin production (9). Injection of PVL positive MRSA causes a rapidly fatal (20% survive 24 hours) necrotizing pneumonia in immunocompetent mice via transcription of genes coding for secreted and cell wall-anchored proteins including lung inflammatory factor staphylococcal protein A (10). Additionally, intranasal inoculation of 4-8 × 10 8 (but not 8 × 10 7 ) CFU of S. aureus Newman, a human clinical isolate, causes a rapidly fatal model of pneumonia in immunocompetent C57Bl/6 mice with evidence of bacterial growth in vivo associated with production of sortase A (11).…”
Section: Introductionmentioning
confidence: 99%
“…Broadspectrum immunosuppression with systemic cyclophosphamide and impairment of mucociliary clearance with intranasal formalin also allow for development of S. aureus pneumonia, independent of bacterial toxin production (9). Injection of PVL positive MRSA causes a rapidly fatal (20% survive 24 hours) necrotizing pneumonia in immunocompetent mice via transcription of genes coding for secreted and cell wall-anchored proteins including lung inflammatory factor staphylococcal protein A (10). Additionally, intranasal inoculation of 4-8 × 10 8 (but not 8 × 10 7 ) CFU of S. aureus Newman, a human clinical isolate, causes a rapidly fatal model of pneumonia in immunocompetent C57Bl/6 mice with evidence of bacterial growth in vivo associated with production of sortase A (11).…”
Section: Introductionmentioning
confidence: 99%
“…This also extends the finding of previous case studies reporting that MRSA CAP with PVL toxin is associated with worse outcomes. [24][25][26][27][28][29][30] Moreover, we clearly document that PVL-positive strains are emerging as a cause of pulmonary infection in broader clinical scenarios. As such, physicians must remain vigilant for this toxin-producing strain.…”
Section: Discussionmentioning
confidence: 89%
“…23 Recent studies of acute pneumonia with animal models and in humans have suggested that the PVL toxin-alone or in combination with other virulence factors-is associated with the development of necrotizing pneumonia. [24][25][26][27][28][29][30] In our study, 23 patients with MRSA CAP had strains that contained PVL toxin, and these patients had longer stays in hospital and higher total hospital charges than those with MRSA CAP not containing the PVL toxin. This is an important finding, as length of stay is an important proxy for morbidity and case severity.…”
Section: Discussionmentioning
confidence: 93%
“…In vitro experiments have demonstrated that the activation of NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) signaling pathway in infected pulmonary epithelial cells results in inflammation enhancement via IL-8 expression; furthermore, intracellular S. aureus can lead, after an initial lag period, to the apoptosis of these cells. [21,22] In necrotizing pneumonia, the key virulence factors of S. aureus associated with the apoptosis of lung cells were shown to be pore-forming toxins, namely Panton-Valentine leukocidin (PVL) and alpha-hemolysin [23,24]. …”
Section: Impact Of Viral Infections In the Respiratory Tract On Staphmentioning
confidence: 99%